Lesser Cornstalk Borer, Elasmopalpus lignosellus (Zeller) (Insecta: Lepidoptera: Pyralidae) - John L. Capinera (EDIS)
This species occurs widely in the western hemisphere and is known from much of the southern United States. Despite its wide distribution, damage is limited principally to sandy soil, so it tends to cause injury in the coastal plain of the southeastern states from South Carolina to Texas. This document is EENY-155, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: September 2000. Revised: November 2005.